2018
DOI: 10.1101/258723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating healthcare and research genetic data empowers the discovery of 49 novel developmental disorders

Abstract: SummaryDe novo mutations (DNMs) in protein-coding genes are a well-established cause of developmental disorders (DD). However, known DD-associated genes only account for a minority of the observed excess of such DNMs. To identify novel DD-associated genes, we integrated healthcare and research exome sequences on 31,058 DD parent-offspring trios, and developed a simulation-based statistical test to identify gene-specific enrichments of DNMs. We identified 299 significantly DD-associated genes, including 49 not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Singletons in classes 3 and 4 show the same mutational spectrum as the genomic background, suggesting that these represent independent mutation events whose spacing is mainly driven by variation in local ancestry. Since multi-nucleotide mutations are uniquely implicated in the genetic architecture of complex diseases 46 and the evolutionary history of the genome 47 , our findings illustrate how the TOPMed sample will facilitate more refined and robust approaches to interpreting patterns of genetic diversity.…”
Section: Insights Into Mutation Processesmentioning
confidence: 82%
“…Singletons in classes 3 and 4 show the same mutational spectrum as the genomic background, suggesting that these represent independent mutation events whose spacing is mainly driven by variation in local ancestry. Since multi-nucleotide mutations are uniquely implicated in the genetic architecture of complex diseases 46 and the evolutionary history of the genome 47 , our findings illustrate how the TOPMed sample will facilitate more refined and robust approaches to interpreting patterns of genetic diversity.…”
Section: Insights Into Mutation Processesmentioning
confidence: 82%
“…Another recent study found a significant enrichment of de novo missense variants in PRKAR1B in a large sample of 31,058 trio-exomes of children with developmental disorders and their unaffected parents 16 .…”
Section: Introductionmentioning
confidence: 96%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted September 11, 2020. ; https://doi.org/10.1101/2020.09.10.20190314 doi: medRxiv preprint parents 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Developmental disorders (DD) are a class of diseases frequently caused by pathogenic mutations in protein coding genes 28 that often disrupt the normal process of neocortical development. Therefore, we asked how a set of 299 DD-associated genes that were recently discovered from exome sequencing of DD parent-offspring trios 29 distributed on our spatial LT trajectory. A total of 74 of the 299 DD-associated genes were found in the spatial LT gene set (1.87-fold enrichment, p = 3.2x10 -8 ).…”
mentioning
confidence: 99%